At-line coupling of hollow fiber liquid-phase microextraction to capillary electrophoresis for trace determination of acidic drugs in complex samples - Miková, Blanka; Dvořák, Miloš; Ryšavá, Lenka; Malá, Zdenka; Gebauer, Petr; Kubáň, Pavel (Talanta, 2022)
Direct analysis of complex samples is demonstrated by the at-line coupling of hollow fiber liquid-phase microextraction (HF-LPME) to capillary electrophoresis (CE). The hyphenation of the preparative and the analytical technique is achieved through a 3D-printed microextraction device with an HF located in a sample vial of a commercial CE instrument. The internal geometry of the device guides the CE separation capillary into the HF and the CE injection of the HF-LPME extract is performed directly from the HF lumen. The 3D-printing process ensures uniform dimensions of the devices, their constant position inside the sample vial, and excellent repeatability of the HF-LPME as well as the CE injection. The devices are cheap (∼0.01 €) and disposable, thus eliminating any possible sample-carryover, moreover, the at-line CE analysis of the extract is performed fully autonomously with no need for operator's intervention. The developed HF-LPME/CE-UV method is applied to the determination of acidic drugs in dried blood spot and wastewater samples and is characterized by excellent repeatability (RSD, 0.6-9.6%), linearity (r2, 0.9991-0.9999), enrichment (EF, 29-97), sensitivity (LOD, 0.2-3.4 μg/L), and sample throughput (7 samples/h). A further improvement of selected characteristics of the analytical method is achieved by the at-line coupling of HF-LPME to capillary isotachophoresis (ITP) with electrospray ionization-mass spectrometry (ESI-MS). The HF-LPME/ITP-ESI-MS system facilitates enhanced selectivity, matrix-free analytical signals, and up to 34-fold better sensitivity due to the use of ESI-MS detection and additional on-capillary ITP preconcentration of the HF-LPME extracts.
Keywords: izotachoforéza; léčivé přípravky; Liquid Phase Microextraction; hmotnostní spektrometrie s elektrosprejovou ionizací; Isotachophoresis; Electrophoresis, Capillary; mikroextrakce kapalné fáze; Spectrometry, Mass, Electrospray Ionization; Pharmaceutical Preparations; elektroforéza kapilární